Dialectical thought in Aristotle’s conception of the world: a materialist reinterpretation - Khuat, Nga Thi (Griot : Revista de Filosofia, 2025)
This article explores the dialectical elements embedded in Aristotle’s philosophical conception of the world, with the aim of reevaluating his contributions through the lens of Marxist dialectical materialism. While Aristotle’s system contains idealist elements, particularly in his metaphysical notion of the Prime Mover, his treatment of core concepts such as motion, change, contradiction, and the relationship between form and matter reveals a proto-dialectical logic. The study focuses on Aristotle’s critique of Plato’s Theory of Forms, his theory of the four causes, and his conception of potentiality and actuality, demonstrating how these themes anticipate later developments in Hegelian and Marxist thought. By engaging both classical texts and contemporary Vietnamese scholarship, the paper argues that Aristotle’s thought remains a valuable foundation for understanding the dynamic and contradictory nature of reality. His contributions offer critical insights into the historical continuity of dialectical philosophy and its relevance to present-day theoretical discourse.